Alcohol policy framing in South Africa during the early stages of COVID-19: using extraordinary times to make an argument for a new normal - Andrew Bartlett; Matthew Lesch; Su Golder; Jim McCambridge (BMC, 2023)
Abstract Introduction Public health and alcohol industry actors compete to frame alcohol policy problems and solutions. Little is known about how sudden shifts in the political context provide moments for policy actors to re-frame alcohol-related issues. South Africa's temporary bans on alcohol sales during the COVID-19 pandemic offered an opportunity to study this phenomenon. Methods We identified Professor Charles Parry from the South African Medical Research Council as a key policy actor. Parry uses a Twitter account primarily to comment on alcohol-related issues in South Africa. We harvested his tweets posted from March 18 to August 31, 2020, coinciding with the first two alcohol sales bans. We conducted a thematic analysis of the tweets to understand how Parry framed alcohol policy evidence and issues during these 'extraordinary times.' Results Parry underlined the extent of alcohol-related harm during 'normal times' with scientific evidence and contested industry actors' efforts to re-frame relevant evidence in a coherent and well-constructed argument. Parry used the temporary sales restrictions to highlight the magnitude of the health and social harms resulting from alcohol consumption, particularly trauma, rather than the COVID-19 transmission risks. Parry portrayed the sales ban as a policy learning opportunity (or 'experiment') for South Africa and beyond. Conclusions Crisis conditions can provide new openings for public health (and industry) actors to make salient particular features of alcohol and alcohol policy evidence.